Implementasi Media Pembelajaran Interaktif Berbasis Aplikasi Canva Pada Mata Pelajaran Sejarah Kebudayaan Islam - Fauziah, Zumrotul; Shofiyuddin, Ahmad; Rofiana, Hidayatur (MADINAH, 2022)
Canva is an application that can be accessed using a smartphone or computer. The Canva application is an application used to create posters, comics, brochures, PPT and learning videos. The SKI teachers at Madrasah Tsanawiyah Syi'ar Islam Maibit have used this media from online to offline learning The purpose of this study is to describe the application, inhibiting and supporting factors in the implementation of interactive learning media based on the Canva application in SKI subjects in class VIII Madrasah Tsanawiyah Syi'ar Islam Maibit.This study uses a qualitative approach. The research instruments are interviews, observation and documentation. Then the data sources in this study were the head of the madrasa, class VIII SKI teachers, and students. The data analysis of this research used data reduction, data presentation and verification.Based on the research conducted, the following results were obtained: First, Implementation of Canva-based interactive learning media at the Islamic School of Tsanawiyah Syi'ar in the form of learning videos, illustrated texts, and material brochures that have been made using the Canva application. Second, there are supporting factors in the form of adequate infrastructure so that students can access material easily, the Canva application can be accessed on smartphones making it easier for SKI teachers to edit, and the enthusiasm of students to learn is increasing with the existence of Canva-based learning media. Third, there are inhibiting factors for learning media made using Canva applications in the form of learning videos, material brochures, and illustrated texts include an internet network that must be stable to edit learning media, students who are still not optimal when making presentations while learning using these media, and students are less responsive when there is a question and answer session about the material presented. d create using the Canva app.